The effectiveness of an educational program based on constructive learning (CLM) on developing scientific concepts and the skills of scientific thinking in science textbook among students of eighth grade in directorate of education in Al-Mazar Al-Janoubi - Al-Hawwari, Lamia' Mohammad; Al-Huwaimel, Omar Abdul Razzaq (Journal of Educational and Psychological Sciences, 2021)
This study aimed at investigating the effectiveness of an educational program based on constructive learning model (CLM) in acquiring and developing scientific concepts the skills of scientific thinking among the female students of the eighth grade in the directorate of education in Al-Mazar Al-Janoubi for the academic year (2020-2021). The study used the quasi approach, where a random sample was selected from the study population that consisted of all the female students of the eighth grade, with a total of (910) female students, while the purposive sample consisted of (57) female students and was randomly distributed to two groups: the experimental group and control group. The study instrument included the test of acquiring scientific concepts, with (32) multiple-choice items and the test of scientific thinking skills, with (30) multiple-choice items distributed to five skills (determining the problem, collecting data, determining hypotheses, testing hypotheses, concluding results); their validity and reliability were verified. The researcher developed the educational program, represented by a number of educational activities in the two units of (living beings and their environment, and motion) from the science textbook of the eighth grade, based on the constructive learning model (CLM). The program consisted of (32) periods and was applied to the experimental group during the academic year (2020-2021). The study results showed that the program, which is based on the constructive learning model (CLM) was effective in promoting the students’ acquisition of the scientific concepts and developing their scientific thinking skills, where the mean scores for the experimental group were higher than the control group. The study recommended conducting further experimental studies for similar educational programs that include samples from other educational stages and other textbooks.